2016
DOI: 10.1186/s12904-016-0117-4
|View full text |Cite
|
Sign up to set email alerts
|

Cultural perspectives of older nursing home residents regarding signing their own DNR directives in Eastern Taiwan: a qualitative pilot study

Abstract: BackgroundChinese tradition and culture developed from Taoism, Confucianism, and Buddhism and have influenced ethnic Chinese for thousands of years, particularly thoughts on death. Many ethnic Chinese, particularly older people, refrain from discussing death-related concerns, making it difficult to obtain advance directives, including do-not-resuscitate (DNR) directives, signed independently by older people. This study explored the attitudes of older nursing home residents in Taiwan toward signing their own DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
73
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(83 citation statements)
references
References 17 publications
(58 reference statements)
9
73
1
Order By: Relevance
“…Chinese culture, which is predominantly Confucian, is the main social context in Taiwan. Most Chinese older adults refrain from discussing death‐related topics, which makes advance end‐of‐life care planning difficult . Even for PwD who had expressed their preferences for end‐of‐life decisions, the proportion of discrepancy between patients and their caregivers was 48.3% for tube feeding, 48.5% for CPR and 60.3% for mechanical ventilation in a Taiwanese investigation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chinese culture, which is predominantly Confucian, is the main social context in Taiwan. Most Chinese older adults refrain from discussing death‐related topics, which makes advance end‐of‐life care planning difficult . Even for PwD who had expressed their preferences for end‐of‐life decisions, the proportion of discrepancy between patients and their caregivers was 48.3% for tube feeding, 48.5% for CPR and 60.3% for mechanical ventilation in a Taiwanese investigation .…”
Section: Discussionmentioning
confidence: 99%
“…Even for PwD who had expressed their preferences for end‐of‐life decisions, the proportion of discrepancy between patients and their caregivers was 48.3% for tube feeding, 48.5% for CPR and 60.3% for mechanical ventilation in a Taiwanese investigation . A majority of medical professionals and patients relied more on families’ preferences and physician authority than on patient autonomy . Because it is a Chinese cultural belief that dying relatives become “hungry ghosts” if they are not supplied with artificial nutrition until they die, and because the general public has insufficient understanding of life‐sustaining treatments, Chinese family caregivers are usually reluctant to prevent aggressive interventions.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the findings from a local Chinese study demonstrating that the most common EOL decision‐making pattern in Hong Kong was physician‐initiated and shared decision‐making with the patient/family members (Pang et al., ). Similar pattern exists in Taiwan and China (Lee, Cheng, Dai, Chang, & Hu, ; Zhang, Xie, Xie, & Liu ), as Hong Kong, Taiwan, and China share similar cultures developed from Confucianism, emphasizing family involvement (Bowman & Singer, ). However, most family caregivers had poor knowledge on life sustaining treatments in Hong Kong (Kwok et al., ).…”
Section: Discussionmentioning
confidence: 89%
“…Similarly, in their study of residents in Norwegian nursing homes, Thoresen and Lillemoen (2016) identified a mismatch between the priorities of residents and the focus of ACP conversations. Lee et al (2016) also encountered residents who viewed functional status and happiness in daily life as more important than making treatment choices for a hypothetical future.…”
Section: Discussionmentioning
confidence: 99%